Depression in patients following limb reconstructive surgeries for trauma - Ramanthan, Saraswathi; Solomon, Susan; Sabapathy, S. Raja; Ravichadran, K. (International Journal of Research in Medical Sciences, 2017)
Background: Psychological complications are common following physical trauma and its surgical treatment. Studies on trauma patients are mostly from the Western world and have focussed more on posttraumatic stress disorder and less on depression. Methods: This study was conducted in a tertiary referral centre for trauma in South India. One hundred patients who had undergone limb reconstructive surgeries following trauma were included in the study. The major causes of trauma were occupational accidents and road traffic accidents. Beck depression inventory II was used to diagnose depression. The severity of trauma, impairment in joint motion and sensory impairment were also determined. Association between the variables was assessed using Chi -Square/ Fisher’s exact test. Results: The prevalence of depression was found to be 36% (95% CI: 26.6-45.4). Age between 41 and 60 years, unemployment, severe degree of injury, and the period between three months and one year of trauma were found to have significant association with depression. Conclusions: Depression is common following physical trauma and its surgical treatment. Its early recognition and treatment is important to ensure faster recovery and better quality of life.